An Analysis Of Thorfinn's Peronalities Change In Vinland Saga by Makoto Yukimura - Hikmah Ridha (CV Insan Kreasi Media, 2024)
Thorfinn, the protagonist of the Vinland Saga, in my opinion, has the most altered personality of all the characters in the series, and this study aimed to describe psychological characteristics change from him. The concept that dominates Thorfinn's personality is also described in this study. This study employs a qualitative methodology combined with literary psychology and data analytic tools. David Krench's theory of emotion classification is applied. According to the study's findings, Thorfinn, the protagonist of the Vinland Saga series, exhibited five different emotional classifications: five for love, two for hatred, four for guilt concept, one for self-punishment, and two for grief. Out of those five categories, the concept of love predominated, followed by guilt concept. This illustrates the force of change's potential when compared to other concepts. Thorfinn's complex character development is evident from the Vinland Saga series' protagonist's plot, which shows us all his psychological journey from the worst to the greatest version of himself. Thorfinn appears to be unbeatable as a result.